Selection and experimental study of the linear displacement converter for the automated monitoring system of mine roofs - Inozemtsev Maxim (EDP Sciences, 2021)
The justification of the linear displacement sensors installation in mine workings is described in this paper. The required technical characteristics of the sensors are given. The main types of primary linear displacement converters are presented. The choice of inductive solenoid-type converters and sensors based on linear differential transformers (LVDT) is justified. The advantages and disadvantages of inductive transducers, their accuracy and measurement limits are described, and measuring methods of inductance of the solenoid-type transducers and the converter output signal based on LVDT are considered. The results of sensors experimental studies based on the solenoid-type inductive transducers are presented.